PEMILIHAN DAN BENTUK FUNGSI MODEL EMPIRIK: STUDI KASUS PERMINTAAN UANG KARTAL RIIL DI INDONESIA - Insukindro, Aliman (UGM, 1999)
This paper attempts to introduce and apply some methods of model selection in order to avold a spectification error. In general, the specification error can be indicated by three possibilities which are possible problem with: (1) disturbances, (2) expplanatory variable and (3) parameters. In this paper, our discussion is concetrated on the functional form of our estimable model. The estimated model in this paper is the demand for real currency in Indonesia for the period of 1984 (1) - 1997 (IV).